Tumblr Facts: Antecedents of Self-Disclosure across Different Social Networking Sites - Marcella Bianchi; Rosa Fabbricatore; Daniela Caso (MDPI AG, 2022)
Previous research investigating antecedents of online self-disclosure pointed out two perspectives: social compensation and enhancement hypotheses, showing controversial findings. Furthermore, most contributions have focused on social networking sites (SNSs) considered mainstream, like Facebook and Instagram, and such results are often considered universally valid for all SNSs. Tumblr is a less-studied SNS with peculiar features-such as anonymity, higher control over the presentation of personal aspects, supportive communities-that could particularly lead individuals to self-disclose. As prior contributions highlighted that the features and affordances could define how a medium will be used, this paper aims to investigate the antecedents of online self-disclosure on Tumblr and other mainstream SNSs. We run a survey on 559 Tumblr users (aged 13-70; M = 28.86; SD = 12.34). T-test showed that Tumblr users have a higher willingness to self-disclose on Tumblr compared to another SNSs (t = 22.44, p < 0.001). A path analysis model confirmed the predictive role of some psychological variables on self-disclosure on Tumblr but not on mainstream SNSs. In particular, self-disclosure on Tumblr was predicted by self-esteem, negative emotionality, and preference for online social interactions, which was in turn predicted by social anxiety. These findings partially supported both social compensation and enhancement hypotheses, indicating that the phenomenon is more complex than expected.